The effect of social determinants of health on use of diabetes‐related mobile health applications in older adults with type 2 diabetes - Damilola Adissa; Cody Makinson; Melissa A. Elafros; Kara Mizokami‐Stout; Eva L. Feldman; Brian C. Callaghan; Evan L. Reynolds (Diabetic Medicine, 2026)
Abstract Aims Determine associations between social determinants of health (SDOH) and use of diabetes‐related mobile health (mHealth) applications in older individuals with type 2 diabetes. Methods We identified participants that self‐reported having type 2 diabetes who completed the National Poll on Healthy Aging, a nationally representative survey of older adults in the United States. Co‐primary outcomes were use of mHealth applications to (1) track diabetes medications and (2) track blood glucose levels. SDOH factors included household income, education, health insurance, lack of companionship or social isolation, homeownership and access to technology. Logistic regression models determine associations between SDOH factors and use of mHealth applications, adjusted for age. Results There were 348 participants with type 2 diabetes that completed the survey (mean [SD] age: 65.4 [7.9] years, 44.0% female, 69.5% White). We found 12.4% used mHealth applications to track blood glucose and 5.5% to track diabetes medications. Regression revealed higher income associated with a greater use of mHealth applications to track diabetes medications (OR: 4.3, 95% CI: 1.3–15.3) and blood glucose levels (OR: 52.0, 95% CI: 6.3–716.9). Additionally, older age (OR: 0.9, 95% CI: 0.8–0.99) was associated with decreased odds of using mHealth applications to track medications, whereas having graduate education (OR: 3.9, 95% CI: 1.2–12.8) was associated with increased odds of using mHealth applications to track blood glucose levels. Conclusions We found that few older adults with type 2 diabetes use mHealth applications to assist in diabetes care, particularly among those with lower income. Future studies are needed to identify barriers and facilitators of mHealth use in these populations to develop and tailor future interventions.